Competitive analysis of footwear industry of São Paulo state (Revista de Administração, 2008)
In the late nineties it was noticed an international adoption of public and private strategies aiming exportation growth and a local supported development. These initiatives demanded, from governs, industries, suppliers, R&D and ST&I institutions, class representatives among others, a search for a larger integration leading them to competitive advantages decurrent of this proximity. This factor, allied to historical and cultural aspects, impelled the arising of clusters in Brazil. This work presents the shoe manufacturer clusters in the State of Sao Paulo and how its agents are organizing themselves aiming the construction and consolidation of competitive advantages. It was used the quantitative methodology in this research and it was due through the study of multiple cases. During this study, competitive factors and sub factors in the shoe manufacturer clusters were identified. These factors were analyzed according to its importance to the cluster's competitiveness as a whole, as well as their developmental level in the analyzed cluster, according to the perception of each researched agent. The research revealed that the involvement level of each of the agents in the analyzed clusters varies from one city to another. Besides, each cluster prioritizes different factors in the search of major competitiveness to footwear industry in its city.